Research Usage and Social Impact of Crowdsourced Air Traffic Data - Martin Strohmeier (Proceedings, 2020)
Crowdsourced data have played an increasing role in research in the sciences over the past decades. From their early instantiations in the 1990s to the search for extraterrestrial intelligence, the concepts of crowdsourcing and citizen science have gained renewed popularity with the broad availability of big data systems. The OpenSky Network has been a poster child of the successful use of crowdsourced data in research and citizen science for many years, with more than 150 peer-reviewed publications using its data. In this article, we follow the efforts made and the results achieved by the OpenSky Network as a non-profit organization with the mission to advance research in and around aviation. We examine the backgrounds and typical usage patterns of OpenSky’s users, both academic and non-academic. We further look at the social impact of air traffic data, particularly during the COVID-19 crisis, and finally examine ways to improve some existing gaps in the data.